KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMK TIGAMA PEKANBARU - Dwi Aprinita Sari; Dudung Burhanudin; M Nur Mustafa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT This study aimed at finding the ability of students at SMK Tigama in writing Descriptive text. The method of this study was descriptive. The samples were 42 students. The subjects were the first year students of SMK Tigama Pekanbaru. The data were collected by using written test. The results of the test were analyzed by considering the aspects of students’ writing ability. Base on the aspects of writing ability, the findings found that the ability of the first year students at SMK Tigama in ‘content’ aspect was in the medium level by the average of 27.610 or 78.96% from the maximum score of 35. The students’ ability was low in ‘organization’ aspect with the average scores of 20.523 or 68.357% from the maximum score of 30. The average score obtained for ‘language use’ was 19.904 or 79.619% from the maximum score of 25. It means that their ability in using the language was in the medium level. In ‘mechanic’ aspect, their ability was low with the average score of 5.66 or 56.66% from the maximum score of 10. In brief, the average score of descriptive writing ability by the first year students was 73.928 or 73.928% from the maximum score of 100. It means that the first year students of SMK Tigama had medium level of ability in writing descriptive text. Key words: Writing, Descriptive text